Analysis of the potential and effectiveness of billboard tax collection in Mimika Regency - Dolame, Penegi; Mollet, Julius Ary; Hutajulu , Halomoan (Goodwood Publishing, 2025)
Purpose: This study aims to (1) assess the potential revenue from billboard tax in Mimika Regency, (2) evaluate the effectiveness of billboard tax collection based on annual revenue targets, and (3) determine its effectiveness based on the actual revenue potential. Research/methodology: This research adopts a quantitative descriptive approach using secondary data from 2019 to 2024, collected from the Regional Revenue Agency (BAPENDA) of Mimika Regency. Data collection was conducted through documentation and interviews. Advertising tax potential was calculated using the formula P=R×S×D×PrP = R× S× D× PrP=R×S×D×Pr, while effectiveness was analyzed using standard ratios compared to both revenue targets and estimated tax potential. Results: The billboard tax potential in Mimika Regency showed consistent growth, from IDR 3.9 billion in 2019 to IDR 6.2 billion in 2024. Tax revenue consistently exceeded annual targets, with an average effectiveness ratio of 107.71%, categorized as very effective. However, effectiveness based on potential was relatively low, averaging 60.81%, indicating a significant gap between potential and actual revenue collection. Conclusions: While the tax collection based on set targets is highly effective, the overall revenue still falls short of the actual potential, reflecting underutilized sources. This implies the need for improved tax object data collection and more optimal revenue management. Limitations: The study is limited to secondary data analysis from a single regional agency, which may not fully capture taxpayer compliance behavior or enforcement challenges. Contribution: This study contributes to local fiscal policy by highlighting the gap between revenue potential and realization, offering insights for optimizing regional tax collection strategies.